The level of teachers' job satisfaction in secondary schools of East Darfur state in Sudan - Ali Elssalih, Elssadig (Technium Social Sciences Journal, 2021)
The purpose of the study was to investigate teachers’ job satisfaction in secondary schools of East Darfur state in Sudan. The sources of data for this research remained secondary school teachers and school principals. The primary data collection instrument was questionnaire for teachers. Besides, the sample school principals was an interview. The sample consists of 650 teachers and ten principals. Teachers were selected using simple random sampling; the school principals were selected using purposive sampling. The questionnaire was distributed to 284 teachers, and the interview was administered to 8 principals, 284 teachers, and eight principals who filled in the questionnaire and returned them. Descriptive statistics, one-sample t-test, and ANOVA test were employed in this study using SPSS to analyze the quantitative data. The qualitative data were analyzed utilizing the thematic analysis method and interview. The study's main findings indicated that there is statistical significance since it is P <0.5. There is a lower level of teachers’ job satisfaction in secondary schools of East Darfur state. One-Way ANOVA showed that were statistically significant differences between groups about the teachers’ job satisfaction of the variables. In conclusion, the teachers ‘satisfaction in secondary schools requires continuous support to raise the level of school teachers. The paper proposed research recommendations and significant suggestions. Since this study was delimited only to education in Eldaien within a single locality, in East Darfur State, the findings lack comprehensive and generalizability of the area. As a result, researchers are recommended to undertake similar research secondary schools at the national level and develop all-embracing and superior findings.